The Bioarchaeology of Dissection and Autopsy in the United States - C. Nystrom, Kenneth (Bioarchaeology and Social Theory, 2017)
Encountering evidence of postmortem examinations - dissection or autopsy- in historic skeletal collections is relatively rare, but recently there has been an increase in the number of reported instances. The Bioarchaeology of Dissection and Autopsy brings together in a single volume the skeletal evidence of postmortem examination in the United States. Ranging from the early colonial period to the early 1900's, from a coffeehouse at Colonial Williamsburg to a Quaker burial vault in lower Manhattan, the contributions to this volume demonstrate the interpretive significance of a historically and theoretically contextualized bioarchaeology. The authors employ a wide range of perspectives, demonstrating how bioarchaeological evidence can be used to address a wide range of themes including social identity and marginalization, racialization, the nature of the body and fragmentation, and the emergence of medical practice and authority in the United States.